Gestión administrativa y su incidencia en la atención al cliente del sindicato de choferes profesionales del cantón La Maná - Lozada Chevez, Lenin Gustavo (2023)
In the 21st century, globalization requires skills to obtain clients. The market is increasing competitiveness with high demands for good service, however, there is a problem in relation to the administrative management whose incidence is more affected in customer service. According to this, the deficient control and training of its collaborators is presented; so that there is lack of continuous improvement in all the activities in the institution. The objective of the research project was to analyze the administrative management and its impact on customer service at the service STATION OF THE PROFESSIONAL DRIVERS’ UNION IN LA MANÁ CANTON, and to solve this problem through strategies that promote better customer service. The research was descriptive and field type. The study population are formed by the clients that constitute 10560 people who frequently use the service station, however, the sample was focused on 269 clients to whom a survey was applied. In addition, an interview was conducted to the secretary of the labor union of drivers. The results in general reported that more than 50% consider that the dispatcher's presentation is regular, the conditions of the service station are in a regular order, and they stated that there is poor customer service. The application of the SWOT analysis determined that there are weaknesses that exceed the strengths of the service station due to the fact that the image of the dispatcher is not adequate to the clients and another observations expressed by the users. As opportunities, there are possibilities for improvement, but the threats outweigh them. In conclusion, it is evident that the service station does not have an adequate administrative management model that helps to satisfy each of its customers, so it is important to apply strategies that promote improvements.